Pengaruh Pendidikan Kesehatan Terhadap Sikap Remaja Tentang Kesehatan Reproduksi - Yulianti, Christy; Suciawati, Anni; Rukmaini, Rukmaini (Universitas Aisyah Pringsewu (UAP) Lampung, 2022)
Adolescents have very complex problems along with the transition period they experience. The prevalence of smoking in adolescents aged 10-18 years has increased from every year, in 2018 of 9.1%, an increase from 2017 of 8.8% and 2013 of 7.2%, 7% of young women have become mothers, 5 % have given birth, 2% are pregnant with their first child. Adolescent girls who have had sexual intercourse as much as 7.6%, teenage boys who have had sexual intercourse as much as 88.5%. This study aims to determine The influence of health education on adolescent attitudes about reproductive health in Durian Payung Village, Tanjung Karang Pusat District in 2021. This type of research is an experimental study with a pre-experimental design and a one-group pretest-posttest design. The sample in this study were 30 teenagers in Durian Payung Village, Tanjung Karang Pusat District. The sampling technique used is random sampling. The research instrument consisted of attitude questionnaires about reproductive health in adolescents. This questionnaire has been tested for validity and reliability with Cronbach's alpha coefficient value of 0.76. Data were analyzed using univariate and bivariate, namely Wilcoxon to determine differences in attitude scores in one group. The results showed that there was an effect of health education on adolescent attitudes about reproductive health in Durian Payung Village, Tanjung Karang Pusat District in 2021 with p-value of 0.000 less than 0.05. Conclusion health education can improve adolescent attitudes about reproductive health. Today's youth should have understood education about reproductive health so that it is not easy for sex violations to occur. Abstrak: Remaja memiliki masalah yang sangat beragam sejalan dengan masa perkembangan yang dialaminya. Prevelensi merokok pada remaja usia 10-18 tahun terjadi peningkatan dari setiap tahunnya, di tahun 2018 sebesar 9,1%, meningkat dari tahun 2017 sebesar 8,8% dan 2013 sebesar 7,2%, 7% remaja wanita sudah menjadi ibu, 5% sudah melahirkan, 2% sedang hamil anak pertama. Remaja perempuan yang sudah melakukan hubungan seksual sebanyak 7,6%, remaja laki-laki yang sudah melakukan hubungan seksual sebanyak 88,5%. Penelitian ini bertujuan untuk mengetahui pengaruh pendidikan kesehatan terhadap sikap remaja tentang kesehatan reproduksi di Kelurahan Durian Payung Kecamatan Tanjung Karang Pusat tahun 2021. Jenis penelitian ini adalah studi eksperimen dengan rancangan pre eksperiment dan desain one group pretest-posttest. sampel dalam penelitian ini adalah 30 remaja di Kelurahan Durian Payung Kecamatan Tanjung Karang Pusat. Teknik sampling yang digunakan yaitu random sampling. Instrumen penelitian terdiri dari kuesioner sikap tentang kesehatan reproduksi pada remaja. Kuesioner ini telah diuji validitas dan reliabilitas dengan nilai koefisien cronbach’s alpha 0,76. Data dianalisis menggunakan univariat dan bivariat yaitu wilcoxon untuk mengetahui perbedaan skor sikap dalam satu kelompok. Hasil penelitian menunjukkan bahwa ada pengaruh pendidikan kesehatan terhadap sikap remaja tentang kesehatan reproduksi di Kelurahan Durian Payung Kecamatan Tanjung Karang Pusat tahun 2021 dengan p value 0,000 kurang dari 0,05. Kesimpulan pendidikan kesehatan mampu meningkatkan sikap remaja tentang kesehatan reproduksi. Saran remaja masa kini seharusnya sudah memahami pendidikan mengenai kesehatan reproduksi agar tidak mudah terjadi pelangaran seks.